Electrocardiogram changes due to sodium stibogluconate treatment of kala-azar - Alom, M. Shamshul; Ali, M. Liaquat; Shaikh, Abdul Alim; Kabir, Jakaria (International Journal of Research in Medical Sciences, 2023)
Background: Kala-azar [visceral leishmaniasis (VL)] is caused by the protozoon Leishmania donovani complex. Without adequate treatment, most patients with clinical VL die due to secondary infections. Pentavalent antimonial compounds are commercially available as sodium stibogluconate and meglumine antimoniate. Sodium stibogluconate remains the mainstay of treatment in most parts of the world. The aim of the study was to evaluate the serious adverse effects of sodium stibogluconate in the treatment of kala-azar (VL). Methods: The study was carried out in the medicine department of North Bengal Medical College Hospital, Sirajganj during the period of June 2021 to December 2021. It was a descriptive cross-sectional study with a sample size of 30. Complete history taking and physical examination were done and recorded in a case record form. At least 7 electrocardiograms (ECGs) were done (1 before treatment, 5 during treatment weekly intervals, and 1 after completion of treatment). Results: In ECG, the following changes were noted (the rhythm, T wave amplitude, ST segment, and QTc interval). Out of 30 patients, 19 patients (63.33%) developed abnormalities in ECG. Among them, 14 patients (46.67%) developed prolongation of QTc interval, 6 patients developed T wave inversion, and 1 patient developed transient 1st-degree heart block. No patients developed symptomatic arrhythmia. Conclusions: Kala-azar is prevalent among the poor in Bangladesh and can be fatal without treatment. Sodium stibogluconate has been associated with cardiological adverse effects, but it can be used safely with proper monitoring.